2001
DOI: 10.1538/expanim.50.365
|View full text |Cite
|
Sign up to set email alerts
|

Production of Transgenic Rats Using Young Sprague-Dawley Females Treated with PMSG and hCG.

Abstract: Abstract:The aim of this study was to examine the effects of gonadotrophin treatments on estrus synchronization and superovulation in young Sprague-Dawley (SD) rats that had not yet exhibited defined estrus cycles (5 to 7 weeks old), and to produce transgenic rats using these females as embryo donors and recipients. In Experiment 1, female rats were injected with PMSG and hCG (12.5, 25, 50 and 100 IU/kg each) and were mated with stud males. The reproductive performance of young rats were highest when PMSG and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 20 publications
5
23
0
Order By: Relevance
“…This result is probably caused by age difference of sensitivities to exogenous hormones. In this study, the doses of injected PMSG and hCG were uniformly 150 and 75 IU/ kg body weight, respectively, while it was previously reported that, using SD strain rats in the pre-pubertal stage, the effect of superovulation was the highest when both PMSG and hCG were injected at the dose of 300 IU/kg body weight [6]. According to that report, the superovulatory response should be improved by adjustment of the dose of injected gonadotrophins.…”
Section: Discussionmentioning
confidence: 77%
“…This result is probably caused by age difference of sensitivities to exogenous hormones. In this study, the doses of injected PMSG and hCG were uniformly 150 and 75 IU/ kg body weight, respectively, while it was previously reported that, using SD strain rats in the pre-pubertal stage, the effect of superovulation was the highest when both PMSG and hCG were injected at the dose of 300 IU/kg body weight [6]. According to that report, the superovulatory response should be improved by adjustment of the dose of injected gonadotrophins.…”
Section: Discussionmentioning
confidence: 77%
“…Rats were superovulated by intraperitoneal i n j e c t i o n s o f 1 5 0 I U / k g e q u i n e c h o r i o n i c gonadotrophin (eCG; Nippon Zenyaku, Co., Fukushima, Japan) at 09:00 on the first diestrous day and 75 IU/kg human chorionic gonadotrophin (hCG; Sankyo, Co., Tokyo, Japan) after an interval of 48 h, as described previously [10]. The rats were then copulated at 18:00 with fertile Wistar male rats.…”
Section: Collection Of Zygotes / Embryosmentioning
confidence: 99%
“…Our first priority was to design a working protocol to determine the ovulation kinetics of three rat strains, Wistar, ACI/N and Fisher, by using a single dose of PMSG and hCG. In spite of the time for oocyte collection reported in the literature being variable (Mukumoto et al 1995, Hirabayashi et al 2001, Krivokharchenko et al 2003, our results demonstrated that 24 h after hCG injection was the most adequate time to harvest the oocytes in the three rat strains. These data agree with other reports (Tain et al 2000, Popova et al 2002.…”
Section: Discussionmentioning
confidence: 57%
“…Production of ES cells in rats is somehow limited by the fact that superovulation protocols have not been optimized for the production of high-quality embryos. Although superovulation protocols for rat have already been published, they mainly focused on the production of either oocytes or zygotes (Mukumoto et al 1995, Tain et al 2000, Hirabayashi et al 2001, Corbin & McCabe 2002, Popova et al 2002, Krivokharchenko et al 2003, and the techniques for the production of morulae or blastocysts are still not well defined (Tain et al 2001, Ishigame et al 2004. Since both morulae and blastocysts are the source of ES cells (Evans & Kaufman 1981, Capecchi 1989, Iannaccone et al 1994, Ouhibi et al 1995, Thomson et al 1998, Vassilieva et al 2000, it would be useful to improve the superovulation protocols that allow obtaining embryos suitable for ES cell production.…”
mentioning
confidence: 99%